The Location Decisions of Foreign Investors in China: Untangling the Effect of Wages Using a Control Function Approach - Liu, Xuepeng; Lovely, Mary E; Ondrich, Jan (The Review of Economics and Statistics, 2010)
There is almost no support for the proposition that capital is attracted to low wages from firm-level studies. We examine the location choices of 2,884 firms investing in China between 1993 and 1996 to offer two main contributions. First, we find that the location of labor-intensive activities is highly elastic to provincial wage differences. Generally, investors' wage sensitivity declines as the skill intensity of the industry increases. Second, we find that unobserved location-specific attributes exert a downward bias on estimated wage sensitivity. Using a control function approach, we estimate a downward bias of 50% to 90% in wage coefficients estimated with standard techniques.